The Saigon times weekly No 2 - '17 (1320) (Ho Chi Minh City Saigon times group, 2017)
Contents of the magazine presented about Inside Vietnam: coffe export, FDI,....; business: banking, corridor,....; living: culture, urban life,....
Keywords: Tạp chí